Anesthetic Influence on Occurrence and Treatment of the Trigemino-Cardiac Reflex. Issue 18 (May 2015) - Meuwly, Cyrill; Chowdhury, Tumul; Sandu, Nora; Reck, Martin; Erne, Paul; Schaller, Bernhard; Gharaei., Helen
<x xml:space="preserve">Abstract</x> Abstract Trigeminocardiac reflex (TCR) is defined as sudden onset of parasympathetic dysrhythmia including hypotension, apnea, and gastric hypermotility during stimulation of any branches of the trigeminal nerve. Previous publications imply a relation between TCR and depth of anesthesia. To gain more detailed insights into this hypothesis, we performed a systematic literature review. Literature about occurrence of TCR was systematically identified through searching in Cochrane Central Register of Controlled Trials (CENTRAL), PubMed (MEDLINE), EMBASE (Ovid SP), and the Institute for Scientific Information (ISI Web of Sciences) databases until June 2013, as well as reference lists of articles for risk calculation. In this study, TCR was defined as drop in mean arterial blood pressure and heart rate, both >20% to baseline. We calculated intraoperative cerebral state index (CSI) of each TCR-case using a newly developed method. These data were further divided into 3 subgroups: CSI <40 (deep anesthesia), CSI 40–60 (regular anesthesia), and CSI >60 (slight anesthesia). Including 45 studies with 910 patients, 140 (15%) presented with TCR, and 770 (85%) without TCR during operation. TCR occurrence showed a 1.2-fold higher pooled risk slighter anesthesia (CSI <40: 13%, at CSI 40–60: 21%, and at CSI >60: 27%) compared with deeper anesthesia. In addition, we could discover a 1.3-fold higher pooled risk of higher MABP drop with a strong negative correlation (r = −0.935; r2 = 0.89) and a 4.5-fold higher pooled risk of asystole during TCR under slight anesthesia compared with deeper anesthesia. Our work is the first systematic review about TCR and demonstrates clear evidence for TCR occurrence and a more severe course of the TCR in slight anesthesia underlying the importance of skills in anesthesia management during skull base surgery. Furthermore, we have introduced a new standard method to calculate the depth of anesthesia.